The effect of high-temperature alteration of oceanic crust on the potassium isotopic composition of seawater. (15th December 2022) - Santiago Ramos, Danielle P.; Nielsen, Sune G.; Coogan, Laurence A.; Scheuermann, Peter P.; Seyfried, William E.; Higgins, John A.
Abstract: High-temperature hydrothermal alteration of oceanic crust is one of the two main sources of potassium (K) to the oceans, with modern flux estimates ranging roughly from ∼8 to 30 % of the K flux from rivers. Despite the role of high-temperature hydrothermal fluids in the global seawater K budget, little is known about its effect on the K isotopic composition of the oceans. Here we present stable K isotope measurements (δ 41 KSRM3141a ) of globally distributed high-temperature hydrothermal fluids from three mid-ocean ridge systems: the East Pacific Rise (n = 21), the Juan de Fuca Ridge (n = 34), and the Mid-Atlantic Ridge (n = 18). We find a strong correlation between δ 41 K and Mg/K ratios, consistent with conservative mixing between a high-temperature hydrothermal fluid (i.e., Mg = 0) and seawater as fluids ascend to the seafloor and/or due to seawater entrainment during sampling. The δ 41 K of end-member hydrothermal fluids is found to range between −0.80 ‰ and 0.07 ‰, with an average value of −0.36 ± 0.30 ‰ (2σ, n = 38). Most (∼76 %) of the variability in end-member fluid δ 41 K compositions observed here can be explained by high-temperature fluid-rock K exchange, with little (∼0.2 ‰) to no K isotope fractionation between hydrothermal fluid and altered crust. Larger deviations from the average end-member hydrothermal fluid value are likely to result from processes other than high-temperature fluid-rock exchange, such as (1) low-temperature hydrothermal reactions during fluid recharge, (2) reaction of fluids with local sedimentary sources, and (3) phase separation. The K contents of end-member fluids vary considerably, from ∼1 to 38 mM, thus a K-weighted average of −0.37 ± 0.24 ‰ (2σ, n = 38) is estimated to represent the δ 41 K composition of the global hydrothermal K flux. Our results suggest that K sourced from axial hydrothermal alteration does not contribute to the elevated 41 K/ 39 K of seawater compared to bulk silicate Earth (BSE). In addition, subduction of oceanic crust altered under high-temperature conditions is unlikely to be a significant source of K isotopic heterogeneity to Earth's mantle.